Epistemology of Hadith Understanding: a Theoretical Study - Umayah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Scolars agree that hadith is the second source of Islamic teachings after the Qur'an. Thus, the hadith serves as an explanatory for the Qur'an. To understand the hadith requires the study of both studies from the sanadnya aspect and studies from the matan aspect. In this paper, the author focuses more on studying the epistemology of understanding hadith in terms of theory. Epistemology is a theory of science, while the understanding of hadith is what Muslims need to make hadith a second guideline after the Qur'an. This paper examines theories related to epistemology, understanding hadith and epistemology in understanding hadith